2017
DOI: 10.1063/1.4996512
|View full text |Cite
|
Sign up to set email alerts
|

Measurement-enhanced quantum search

Abstract: Abstract. The oscillatory nature of the unitary Grover operator makes quantum searching difficult if one has no prior knowledge of the number of target states in the database. In this work, we coupled the database to an external qubit to transfer the target state in a space where the quantum search operation is not applied. This is followed by a measurement of the external and the ancilla qubit which result to a mixed state with a higher probability of finding the target state. The algorithm is simulated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The input layer will take the cross-section values on the energy points (0, 100 MeV). Other architectures were considered in a previous study (Sombillo, et al, 2020) and found that the hidden layer with architecture (250-100-50) performed better than the other architecture considered in the same study. The full analysis and the codes used are accessible in the author's online code repository (Sombillo, 2020).…”
Section: Optimization Of Dnn Modelmentioning
confidence: 85%
“…The input layer will take the cross-section values on the energy points (0, 100 MeV). Other architectures were considered in a previous study (Sombillo, et al, 2020) and found that the hidden layer with architecture (250-100-50) performed better than the other architecture considered in the same study. The full analysis and the codes used are accessible in the author's online code repository (Sombillo, 2020).…”
Section: Optimization Of Dnn Modelmentioning
confidence: 85%